Characteristics of Pregnant Women with Reactive HBsAg - Rosmawati Lubis; Shinta Novelia; Hayatun Nufus (KHD Production, 2023)
In developing countries, including Indonesia, vertical hepatitis B virus transmission still plays an essential role in spreading the hepatitis B virus. The first step in preventing vertical transmission is knowing the HBsAg status of pregnant women. The HBsAg screening method for pregnant women using a rapid test was carried out by the Hepatitis B Early Detection Activity (DDHB) for pregnant women at the Puskesmas and its network. In order to break the chain of hepatitis B transmission from mother to baby, health workers play an essential role in this, especially midwives. Because midwives are health workers closest to pregnant women, all pregnant women are expected to have their HBsAg status checked to know whether they have hepatitis B disease or not. This study aims to determine the relationship between the factors of pregnant women and the incidence of positive HBsAg where the characteristics include age, occupation, parity, environment, number of sex partners, history of blood transfusion, and history of hepatitis B immunization in the Taktakan district of Serang City, Banten. This study used an observational study with a case-control approach, and the case sampling technique was purposive sampling. The sample of this study was 80 pregnant women, with a total of 40 people from the case group and 40 people from the control group with a ratio of 1: 1. The research instrument consisted of a pregnant woman's early detection questionnaire at each pregnant woman's blood sampling. This questionnaire is in the Ministry of Health's program. In this study, it was found that there was a relationship between the characteristics of pregnant women based on the environment, the number of sex partners, and a history of hepatitis B immunization with the incidence of positive HBsSg in the Taktakan District, Serang City (Sig value > 0.05). As for the other variables in this study, there was no relationship between the characteristics of pregnant women based on age, occupation, parity, and history of blood transfusion with the incidence of positive HBsAg in the Taktakan District, Serang City (Sig value < 0.05). There is a relationship between the characteristics of pregnant women based on the environment, the number of sex partners, and a history of hepatitis B immunization with the incidence of positive HBsAg in the Kecamatan Taktakan, Serang City. Researchers hope that further research can continue with more diverse variables and samples.